2016
DOI: 10.1007/s10549-016-4010-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine and breast cancer survival in the Health, Eating, Activity, and Lifestyle Study

Abstract: Purpose Use of complementary and alternative medicine (CAM) is common among breast cancer patients, but less is known about whether CAM influences breast cancer survival. Methods Health Eating, Activity and Lifestyle (HEAL) Study participants (n=707) were diagnosed with stage I–IIIA breast cancer. Participants completed a 30-month post-diagnosis interview including questions on CAM use (natural products such as dietary and botanical supplements, alternative health practices and alternative medical systems), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Some others also call this therapy a holistic treatment. This is based on the type of therapy that impacts the individual in general--that is, his harmony to integrate mind, body, and soul in a unity (Neuhouser et al, 2017;Smith, Duell, & Martin, 2004). Thus, it can be concluded that complementary therapy is a traditional therapy that adjoins the modern one to thoroughly integrate the patient's mind, body and soul as one function.…”
Section: Discussionmentioning
confidence: 99%
“…Some others also call this therapy a holistic treatment. This is based on the type of therapy that impacts the individual in general--that is, his harmony to integrate mind, body, and soul in a unity (Neuhouser et al, 2017;Smith, Duell, & Martin, 2004). Thus, it can be concluded that complementary therapy is a traditional therapy that adjoins the modern one to thoroughly integrate the patient's mind, body and soul as one function.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, it is difficult for patients to draw firm conclusions on whether this therapy goal has been achieved, and no links have been established between the use of integrative medicine and disease prognosis or mortality. 15 However, a fear of tumor recurrence has been found to be associated with the use of CAM by patients. 36 Overall, almost 90% of the patients included in the present study stated that they had achieved mind-body stabilization.…”
Section: Discussionmentioning
confidence: 99%
“… 9 - 11 The most important and most frequently used complementary methods in Germany are: sport and exercise, nutrition therapy, nutritional supplements, phytotherapy, traditional homeopathy, mistletoe therapy, acupuncture, and relaxation techniques. 11 - 15 …”
Section: Introductionmentioning
confidence: 99%
“…NIH has classified CAM into four categories: (1) mind and body medicine (meditation, yoga, acupuncture, guided imagery, qi gong), (2) manipulative and body-based practices (spinal manipulation, massage therapy, chiropractic medicine), (3) alternative systems (traditional Chinese medicine, Native American healing systems, Reiki, homeopathic medicine, Ayurveda), and (4) natural products (herbal supplements, botanical supplements, single supplements, and combinations of vitamins or minerals) ( 152 ). In addition to these, electrotherapeutic modalities, such as LASER, electrical stimulation, microwave diathermy, and thermotherapy have demonstrated insufficient evidence to support their use ( 153 ).…”
Section: Complementary Therapies and Alternative Medicine (Cam)mentioning
confidence: 99%